Evaluating the Efficacy of Using Predifferentiated and Enriched Mathematics Curricula for Grade 3 Students: A Multisite Cluster-Randomized Trial. (October 2014) - McCoach, D. Betsy; Gubbins, E. Jean; Foreman, Jennifer; Rubenstein, Lisa DaVia; Rambo-Hernandez, Karen E.
Despite the potential of differentiated curricula to enhance learning, limited research exists that documents their impact on Grade 3 students of all ability levels. To determine if there was a difference in achievement between students involved in 16 weeks of predifferentiated, enriched mathematics curricula and students using their district's curricula, we conducted a multisite cluster-randomized control trial with 43 schools in 12 states. A series of three-level models, using pre- and postachievement test data, failed to show a main effect for treatment, but the results suggested a treatment by achievement-level interaction that was moderated by the achievement level of the school. As a result, the highest achieving students in the lower achieving schools seemed to receive the greatest benefit from the treatment curricula. An analysis of researcher-developed unit tests revealed that treatment students successfully learned and applied the curricula's challenging mathematics. Thus, using the predifferentiated and enriched mathematics curricula with heterogeneous ability students appeared to "do no harm"—students who completed the treatment curricula did as well as their control counterparts, on average. Evidence of its achievement-related benefits is more ambiguous; however, the findings do suggest some benefits for the highest achieving students in lower achieving schools.